Performance of Exotic Cucumber Varieties under Local Cultivation Practices in Kapilvastu District of Nepal - Dhakal, Tikaram; Khanal, Bikash; Maharjan, Salina (International Journal of Environment, Agriculture and Biotechnology, 2023)
A field experiment was carried out in the Western Terai of Nepal, Buddhabhumi municipality of Kapilvastu district to screen out the best-performing cucumber variety among the five most cultivated exotic varieties; LHC-1395, LHC-Maria, Dynasty, NS-408, and Rehmat-1080 during February to July of 2019. The package of cultivation practiced in this study replicates that of the local farmers. The experimental setup was laid on Randomized Complete Block Design having five replications and five treatments in an area of the 750-meter square. The crop geometry was maintained at 25 cm×15 cm and the size of each plot was 1.4 m2. Data was collected on the morphological and yield parameters such as plant height/vine length, number of leaves, number of branches, days to flowering and fruit development, number of fruits, fruit weight, and fruit yield per plant. The study revealed that the performance of Dynasty was best in terms of plant height with an average increase in height of 23.9 cm per week. LHC-1395 was demonstrated to be the variety with the highest increase in leaf number with an average of 2.08 leaves per week. Similarly, the highest number of branches was found to develop in NS-408 (3.2), the highest number of fruits per plant in LHC-1395 (11.36), the highest single fruit weight in LHC-Maria (208.44 grams), and the highest fruit yield per plant in LHC-1395 (2137.9 grams). Thus, the study concluded that LHC-1395 is a high-yielding variety suited for the study area.